The use of role-playing game (RPG) media in ICT subject to improve learning motivation - Sholichah, Ana Fatwatush; Gunarhadi; Musadad, Aa (AIP conference proceedings, 2022)
This study aimed to examine the effect of android-based Role-Playing Game (RPG) media in ICT (Information and Communication Technology) subject to improve student learning motivation at Junior High School State 40. It used a quasi-experimental method with a pretest-posttest control design. The tests of Role-Playing Game (RPG) media in learning and student motivation were conducted on the research subjects, eighth-grade students of Junior High School State 40 Semarang with cluster random sampling technique. It was found that, based on the scores obtained from the statistical test with the SPSS 20 program, the sig. level was 0.007, less than 0.025 (0.000<0.025). This shows that there is a significant difference in the mean value between control class and experimental class. Therefore, Role-Playing Game (RPG) media affects learning process in classroom, which is shown by increase in student learning motivation.